The Evaluation of Physicochemical and Sensory Properties of Sehati Yogurt Drink Flavors with a Combination of Spice Extract - Latifasari, Nurul; Naufalin, Rifda; Supriyanti, Retno; Nuraeni, Indah; Hartono, Eko Fauzi (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2023)
Yogurt is a popular functional drink that can be flavored and enhanced with a variety of spice extracts. Variants of flavors with a combination of spice extracts increase their uniqueness and practical value because of their bioactive components. However, it is necessary to study the physicochemical characteristics and sensory acceptance after adding the flavor variants of the spice extract combinations produced. This study aimed to determine the physicochemical and sensory attributes of the small and medium enterprise of Sehati yogurt drink, which added the flavor combination of ginger, lemongrass and galangal spice extracts in the kunir asem, wedang uwuh and wedang telang flavor variants. The variations were 5% v/v kunir asem, 5% v/v wedang uwuh and wedang telang 5% v/v and 0% for the control used a completely randomized design (CRD) with five replications. Based on the results, the Sehati yogurt drink with 5% kunir asem flavor variant had the highest viscosity, fat content and carbohydrates with 53.4 cP; 3.15%; and 14.61% respectively. The wedang uwuh flavor variant had the most elevated moisture and ash content with 0.3% and 81.27% respectively while the wedang telang flavor variant had the highest protein content value of 1.74%. Moreover, the highest score in terms of taste (sour), aroma, color, thickness and level of preference (sensory attributes) was the wedang telang flavor variant. This research will contribute to further developing functional drinks combined with traditional spices.